Factors Affecting Fe Tablet Consumption in Adolescent Girls in Order to Prevent Anemia in Mataram City - Tarigan, Rizqy Agung Fattahillah; Cholidah, Rifana; Danianto, Ario (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A disorder known as anemia occurs when the body's hemoglobin level falls. Oxygen is transported throughout the body by hemoglobin. Because puberty alters the body's nutritional and physiological requirements, teenage females are among the groups most at risk for anemia. If adolescent girls' anemia is not addressed with regular Fe pill use, it can impair their capacity to learn and result in pregnancy. Adolescent girls' consumption of Fe pills is influenced by a number of factors, including distribution of the tablets, school assistance, attitude, and knowledge. This study aims to determine the factors that influence the consumption of Fe tablets in adolescent girls. The type of research conducted is an analytical survey study with a cross-sectional approach and using chi-square data analysis with a sample size of 68 respondents. The results of the study showed that the variable level of knowledge was dominated by the less category (50%) and had a p-value of 0.000, the attitude variable was dominated by a positive attitude (54.4%) and had a p-value of 0.061, the school support variable was dominated by the less supportive category (54.4%) and had a p-value of 0.041, the overall distribution variable of Fe tablets received tablets once a week (100%) and the p-value could not be assessed (NA).